Comparison of two teaching methods in immunology for medical students: a quasiexperimental study with nonequivalent control group - Paz-Cevallos, Washington (2026)
The chalk talk and slide projection methods in biomedical science lectures show differences in student learning in the short and medium term, which impacts future therapeutic decision-making in favor of the patient. A 2017 study by the Faculty of Medical Sciences at the Central University of Ecuador reported that 50% of students did not fully understand the lectures. Therefore, a quasi-experimental operational study with a non-equivalent control group was conducted with first-semester medical students during the 2024-2025 academic year to compare the effectiveness of both methods in short- and medium-term learning. Participants were assigned to the interventions: chalk talk and slide projection; and received a Basic Immunology lecture using the respective methodology. Each group was evaluated before, immediately after, and one week after the lecture. The level of learning was estimated using a 20-point test specific to the course. The chalk talk group improved from a pre-intervention mean score of 5.07 ± 2.76 to a post-intervention mean score of 12.92 ± 3.86 and scored 8.33 ± 3.68 one week later (p < 0.05). The slide group improved from a pre-intervention mean score of 6.06 ± 3.29 to a post-intervention mean score of 8.76 ± 3.19, with a score of 6.93 ± 3.57 one week later (p < 0.05). It was concluded that the chalk talk method is more effective than slide projection in the short and medium term for teaching medical students, with no influence from IQ or gender.